Microbiological Profile of Corneal Ulcers at a Tertiary Referral Center - ZARE, Mohammad (Med Hypothesis Discov Innov Ophthalmol, 2019)
The aim of this study was to describe patient demographics, microbiological profile, and antibiotic susceptibility of corneal ulcer at a tertiary referral center to improve and optimize diagnosis and treatment of this potentially blinding entity and to reduce antibiotic misuse. Detailed external and slit-lamp bio-microscopic examination of 123 consecutive patients with suspected corneal ulcer was performed at an ophthalmology clinic. Corneal scraping was carried out under slit-lamp bio-microscopy. The obtained material was inoculated on culture media and smeared on a slide for Gram's staining for morphological identification of bacteria and fungus. For samples that developed colony in culture media, antibiotic susceptibility testing was performed. In a significant percentage of patients (72%) neither bacterial agents nor fungi were the cause of corneal ulcer. Of the 34 culture-proven corneal ulcers, in 79% of the cases, bacteria were detected while in 21% of cases, fungi were found. Of the 27 bacterial corneal ulcers, the majority were (67%) caused by Gram-positive bacteria, of which 50% were Streptococcus pneumoniae, and in the Gram-negative bacterial corneal ulcers, most of the cases (44%) were caused by Pseudomonas aeruginosa. In the antibiotic susceptibility report, Streptococcus pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli were resistant to Cotrimoxazole (TS), Streptococcus pneumoniae to Erythromycin (E), Staphylococcus aureus to Peniciline (PG), Pseudomonas aeruginosa to Ceftriaxone (CRO) and Nitrofurantoin (NI), and finally, Escherichia coli to Gentamicin (GM). In conclusion, in a significant number of the patients neither bacterial agents nor fungi were offending microorganisms and bacteria were the most common agent of microbiological corneal ulcer, found in 79% of culture-proven corneal ulcers, followed by fungus, found in 21% of culture-proven corneal ulcers.